DEVELOPMENT OF A LOCAL GEOID MODEL AT THE FEDERAL DISTRICT, BRAZIL, PATCH BY THE REMOVE-COMPUTE-RESTORE TECHNIQUE, FOLLOWING HELMERT’S CONDENSATION METHOD - Marotta, Giuliano Sant’Anna; Vidotti, Roberta Mary (Boletim de Ciências Geodésicas, 2017)
There are several techniques for determining geoid heights using ground gravity data, the geopotential models, the astro-geodetic components or a combination of them. Among the techniques used, the Remove-Compute-Restore (RCR) technique has been widely applied for the accurate determination of the geoid heights. This technique takes into account short, medium and long wavelength components derived from the elevation data obtained from Digital Terrain Models (DTM), ground gravity data and global geopotential models, respectively. This technique can be applied after adopting the procedures to compute gravity anomalies and, then, the geoid model, considering the integration of different wavelengths mentioned, and their compatibility with the vertical datum adopted. Thus, this paper presents the procedures, involving the RCR technique, following Helmert’s condensation method, and its application to compute one local geoid model for the Federal District, Brazil. As a result, the local geoid model computed for the studied area was consistent with the available values of geoid heights derived from geometrical levelling technique supported by GNSS positioning.